Rights Of Disabilities To Education, Occupation, Health, Social Welfare, And Accessibility - Yopi Harwinanda Ardesa; Prasetyo Catur Utomo; Etanaulia Marsim (Poltekkes Kemenkes Surakarta, 2020)
Background: People with disabilities are those with physical or mental limitations in long term. People with disabilities have some rights they deserve such as rights to education, occupation, health, social welfare, and accessibility. Aims study is to describe Rights of Disabilities to Education, Occupation, Health, Social Welfare, and Accessibility. Methods: This research was conducted on December 2019, in Colomadu Sub District using questionnaire with cross-section design. The subject used consisted of 23 quadriplegic persons. Results: Out of 23 quadriplegic persons, the result of analysis showed significant score of 0.236 between people with disabilities and right to education, of 0.167 between people with disabilities and right to occupation, of 0.313 between people with disabilities and right to health, of 0.150 between people with disabilities and right to social welfare, and of 0.762 between people with disabilities and right to accessibility, with p > 0.05. Conclusion: The rights of people with disabilities (disability people) have not been fulfilled yet in Colomadu Sub District.